Extreme rainfall in Dakar (Senegal): a case study for September 5, 2020 - Diedhiou, Salif; Rauch, Manuel; Lahat Dieng, Abdou; Bliefernicht, Jan; Sy, Souleymane; Sall, Saïdou Moustapha; Kunstmann, Harald (Frontiers in Water, 2024)
West African countries frequently experience extreme rainfall events during the monsoon season. On September 5, 2020, a significant event occurred in the Dakar region of Senegal with daily rainfall totals exceeding 90 mm, causing widespread flooding and displacing 1,000's of people. Despite the severity of this event, the physical mechanisms driving such extreme rainfall remain unexplored. This study aims to investigate the physical mechanisms associated with this event using multiple data sources, including satellite rainfall estimate products (GPM-IMERG, CHIRPS) and reanalysis data (ERA-5). By analyzing wind fields and mid-tropospheric moisture content from reanalysis data, we examined the synoptic-dynamic evolution of the atmosphere and the movement of the cyclonic vortex that transported moisture to the affected region, resulting in substantial rainfall measurements exceeding 100 mm. The analysis also revealed that a vortex over the ocean slowed down the vortex near Senegal, prolonging the rainfall over a total period of 10 h. Additionally, this study presents a comprehensive comparative analysis of state-of-the-art satellite rainfall estimates, assessing their accuracy and reliability in capturing extreme rainfall events both spatially and at specific rainfall gauges situated in Dakar. This evaluation revealed that while satellite rainfall estimates are valuable, they tended to underestimate (up to 40%) the actual rainfall observed at the Dakar-Yoff station. Furthermore, extreme value analysis showed that there is a tendency to underestimate return levels for high-intensity events, with some cases showing underestimations by up to twice the actual values. Thus, this research advances our understanding of extreme rainfall events in West Africa and improves our knowledge of satellite-based rainfall estimates, contributing to future monitoring and preparedness. Furthermore, these findings highlight the importance of monitoring cyclonic systems associated with African Easterly Waves, contributing to a better understanding of extreme rainfall events in West Africa.